2010
DOI: 10.1007/s00204-010-0626-5
|View full text |Cite|
|
Sign up to set email alerts
|

Nephrotoxicity of contrast media and protective effects of acetylcysteine

Abstract: Contrast-induced acute kidney injury (CI-AKI) accounts for approximately 10% of all causes of hospital-acquired renal failure, causes a prolonged in-hospital stay, and represents a powerful predictor of poor early and late outcome. N-acetylcysteine (NAC) is a thiol compound classically known as a mucolytic agent, which is a potent antioxidant that scavenges a wide variety of oxygen-derived-free-radicals and may be capable of preventing acute kidney injury. In the present study, we will review (1) the pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 73 publications
3
31
0
1
Order By: Relevance
“…Measurements from all groups are summarized with plots in Fig. Control group readings for each parameter were within the normal range reported in the literature (13). The rats injected with diatrizoate without pretreatment (group CA) had substantial changes in their biochemistry.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Measurements from all groups are summarized with plots in Fig. Control group readings for each parameter were within the normal range reported in the literature (13). The rats injected with diatrizoate without pretreatment (group CA) had substantial changes in their biochemistry.…”
Section: Resultssupporting
confidence: 67%
“…Past studies have demonstrated that pretreatment with NAC and calpain maintains kidney's normal function (13,19). Therefore, in this study, NAC and calpain were used as reference drugs for the novel pretreatment strategy with propolis.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its antioxidant effect, NAC has dose-dependent protective effects against contrastinduced nephrotoxicity (Briguori et al, 2011). NAC can also be used as both a chelating agent for methylmercury (for review see Dodd et al, 2008) and a mucolytic and antiinflammatory agent, with controversial efficacy in patients with exacerbations of chronic obstructive pulmonary disease (Decramer et al, 2005).…”
Section: N-acetylcysteine In Humans: From Acetaminophen Overdose Antimentioning
confidence: 99%
“…Nephrotoxicity represents one of the cutting-edge topics of our journal (Francescato et al 2011;Stewart et al 2011a, b;Faiz et al 2011;Briguori et al 2011;Song et al 2011;Abdel-Bakky et al 2011;Liu et al 2011;Chattopadhyay et al 2011). Therefore, the editors are pleased that Antonio C. Santos and colleagues from the University of Sao Paulo in Brazil accepted our invitation of a state of the art review on cisplatin-induced nephrotoxicity and strategies of nephroprotection (Santos et al 2012; this issue).…”
mentioning
confidence: 97%